The developing pedagogical and psychological trends and MOOCs: A Systematic Review (Journal of Pharmaceutical Negative Results, 2022)
Massive Open Online Courses (MOOCs) are web-based platforms that have significantly impacted various aspects of education and learning. This practical and qualitative study was conducted using the thematic synthesis method based on the Atridasterling model. This study investigates the effects of MOOCs on pedagogical and psychological trends in scientific research in international and Iranian studies from 2016 to 2021. Therefore, 125 English and 15 Persian articles were selected and analyzed using the purposeful method and theoretical saturation criteria. The qualitative data were analyzed using MAXQDA 2010. The results showed the effectiveness of MOOCs at the international studies, including the estimated efficiency in learning (Individual learning, learning process, Learning product, Social learning), education (Job skills, Identifying the academic problem, Planning and implementation, Course and educational content), psychological( Self-help skills, Cognitive effectiveness, Functional effectiveness, Life Skills, Motivational effectiveness, positive psychology, emotional effectiveness, Learning Social psychology variables) and pedagogical (Education and higher education processes). The effectiveness of MOOCs in Iranian studies includes the fields of learning (learning efficiency), psychology (improving psychological processes in education), education (improving teaching processes), and technology (promoting digital literacy). Finally, according to the findings, MOOCs can influence many dimensions and the nature of pedagogical and psychological processes.